A Holistic Approach to Analyze Systemic Jasmonate Accumulation in Individual Leaves of Arabidopsis Rosettes Upon Wounding - Heyer, Monika; Reichelt, Michael; Mithöfer, Axel (Frontiers in Plant Science, 2018)
Phytohormones, especially jasmonates, are known to be mediators of the plant responses to wounding and herbivore feeding. Their role in such stress responses has been largely studied locally in treated leaves. However, less is known about the induced systemic distribution of phytohormone signals upon these kinds of stresses. Here, a holistic approach was performed in order to investigate the systemic phytohormone pattern in the rosette of Arabidopsis thaliana after herbivore-related wounding. Levels of different stress-related phytohormones such as jasmonates, abscisic acid and salicylic acid were analyzed in individual leaves. We demonstrate that the typically used sampling method, where leaves are first cut and immediately frozen, causes false-positive results since cutting already induces systemic jasmonate elevations within less than 1.6 min. Therefore, this approach is not suitable to study systemic phytohormone changes in the whole plant. By developing a new method where leaves are frozen first and subsequently cut, sampling-induced phytohormone elevations could be reduced. Using this new method, we show that jasmonic acid and its active isoleucine conjugate (jasmonoyl-isoleucine) are involved in the fast systemic wound response of Arabidopsis. A systemic induction of the jasmonates’ precursor, 12-oxo-phytodienoic acid, was not observed throughout our treatments. The systemic phytohormone distribution pattern is strongly linked to the vascular connections between the leaves, providing further evidence that the vascular system is used for long distance-signaling in Arabidopsis. Besides already known vascular connections, we also demonstrate that the systemic distribution of jasmonate signals can be extended to distant leaves, which are systemically but indirectly connected via another vascularly connected leaf. This holistic approach covering almost the whole Arabidopsis rosette introduces a method to overcome false-positive results in systemic phytohormone determinations and demonstrates that wounding-induced long-distance signaling includes fast changes in jasmonate levels in systemic, non-treated leaves.